AUGMENTED REALITY IN VOCABULARY LEARNING: AN INVESTIGATION ON ITS USEFULNESS AND PUPILS’ PERCEPTION - Lau Ann Joe; Azlina Abdul Aziz (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
The formation of the Fourth Industrial Revolution (IR 4.0) is ushering in a new era of technology advancement, artificial intelligence, automation and Internet of Things (IoT), which is making impact not only to the field of manufacturing and industries, but also to education. This new revolution has impacted the advancement in English learning. Learning English is not only about the four skills: listening, speaking, reading and writing; but also, vocabulary learning. However, young learners who are at the initial stage of language and vocabulary acquisition often faced significant challenges such as unattractive teaching and learning, which cause disengagement in the classroom activities. Hence, in this study, Augmented Reality, AR had been actively integrated in the vocabulary acquisition process to improve pupils’ vocabulary learning. This study aims to explore the usefulness of AR flashcards in Year 1 ESL pupils’ vocabulary learning as well as their perceptions towards the use of AR flashcards in their vocabulary learning. The data was collected through action research method. Qualitative data from reflective journal and semi-structured interview were collected and analysed to answer the research questions. The findings of the study revealed that the AR flashcards are useful in sparking pupils’ learning interest and encouraging pupils’ engagement in the lesson. The pupils also showed positive response and expressed their satisfaction towards the use of AR flashcards in their lessons. Finally, the research implications and recommendations were discussed.